Understanding DSM-5-TR: Changes, Updates, and Ethical Practices in Mental Health. - Bobadilla, Tony (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2024)
This overview delves into the DSM-5-TR, exploring its historical development, organization, and significant changes, emphasizing cultural, racist, and discriminatory considerations, coding intricacies, and the assessment of children. The updated criteria for various disorders are examined, with a particular focus on Prolonged Grief Disorder and its associated concerns. Future research suggests enhancing the DSM-5-TR through dimensional approaches and investigating their impact on clinical practice and patient outcomes. Mental health professionals are urged to use the DSM-5-TR effectively and ethically, considering both its strengths and limitations. The paper aims to comprehensively understand the DSM-5-TR and its prospective role in shaping research and clinical practices.